Unravelling the trophic ecology of the ocean sunfish Mola mola in the western Mediterranean Sea through integrated approaches - Oriol Borrajo; Salvador García-Barcelona; Elena Fernández-Corredor; Fernando Ángel Fernández-Álvarez; Marta Coll; Joan Navarro (Reviews in Fish Biology and Fisheries, 2026)
Understanding the trophic ecology of marine megafauna is essential for elucidating their ecological roles and supporting effective conservation strategies. The ocean sunfish ( Mola mola ) is the second-largest bony fish worldwide and has a broad distribution, including the Mediterranean Sea. Despite its size and widespread occurrence, many aspects of its biology remain poorly understood. Traditionally regarded as an obligate feeder on gelatinous zooplankton, recent evidence instead points to a more generalist feeding strategy. Here, we applied a multi-method approach integrating stomach content analysis, DNA metabarcoding, and stable isotope analysis to investigate the feeding ecology of ocean sunfish in the western Mediterranean Sea. Our results revealed that, indeed, ocean sunfish mainly consume gelatinous zooplankton, particularly siphonophores such as Chelophyes appendiculata . However, substantial arthropod, mollusc and chordate contributions were also detected by molecular or observational methods, suggesting a more generalist diet. Stable isotope analysis showed high δ 15 N values compared to other sympatric marine predators reported in the literature, while δ 13 C values showed that ocean sunfish feed extensively in oceanic/pelagic environments. Our results suggest that ocean sunfish in the western Mediterranean Sea occupy an intermediate trophic position but are isotopically segregated from other sympatric marine predators, reflecting a distinct trophic niche. Our integrated approach shows that ocean sunfish play an important role as intermediate predators, facilitating energy transfer from low pelagic trophic levels to higher-level predators, and potentially contributing to the regulation of gelatinous plankton populations.

Past and Future Shifts in Marine Species Distributions Across Two South American Large Marine Ecosystems - Maria Bas; Sofía Diéguez Díaz; Jazel Ouled‐Cheikh; Marta Coll (Journal of Biogeography, 2026)
Aim To quantify temporal (Middle Holocene, historical and future) and spatial changes in habitat suitability for marine species in two South American Large Marine Ecosystems, and to evaluate the ecological consistency of long‐term Species Distribution Model projections using archaeological records as independent evidence of past species occurrences. Location Humboldt Current and Patagonian Shelf Large Marine Ecosystems (LMEs). Time Period Middle Holocene (~8200–4200 years BP), present day (1850–2014), and a projected future warming scenario (2015–2099; SSP5‐8.5). Major Taxa Studied Marine fish, penguins and pinnipeds. Methods SDMs were developed for nine marine species using present‐day occurrence records and contemporary environmental predictors. Models were projected to Middle Holocene climatic conditions and to a future high‐emissions scenario. Archaeological records of fish, penguins and pinnipeds from the Middle Holocene were compiled and used as proxies for past species occurrences to evaluate model projections through time. Results Bathymetry emerged as a key predictor of habitat suitability for most species. Projections revealed pronounced temporal and spatial shifts in suitable habitat. Most fish species showed higher suitability at higher latitudes during the Middle Holocene, followed by contractions in the historical period and future projection. Penguin species exhibited heterogeneous responses, with several showing strong declines in future suitable habitat. Pinniped species displayed mixed patterns of contraction and expansion depending on region and time period. Comparison with archaeological records indicated that seven of the nine SDMs correctly identified suitable habitats consistent with Middle Holocene occurrences. Main Conclusions Zooarchaeological data provide an independent line of evidence to assess the temporal robustness of marine SDMs. Incorporating past climatic periods improves confidence in long‐term biogeographical projections and enhances understanding of species' distributional dynamics under climate change.

Isoscapes of carbon and nitrogen for some pelagic and demersal key species in the western Mediterranean Sea - Elena Lloret-Lloret; María Grazia Pennino; Alba Fuster-Alonso; Marta Coll; José María Bellido; Antonio Esteban; Joan Giménez (Progress in Oceanography, 2026)

A new Western Mediterranean Sea EBSAs proposal based on quantitative information of key criteria - Maria Bas; Miquel Ortega; Francisco Ramírez; Jeroen Steenbeek; Marta Coll (Marine Policy, 2026)

An atlas of climatic predictors for the Sahelian upwelling marine ecosystem region - Iñigo Gómara; Elena Calvo-Miguélez; Belén Rodríguez-Fonseca; Marta Coll; Pablo Ortega (Progress in Oceanography, 2026)

Fisheries Management Models in the Mediterranean Sea: An In‐Depth Review - Salma Aboussalam; Karima Khalil; Marta Coll; Zainab Damsiri; Khalid Elkalay (Fisheries Management and Ecology, 2026)
This study presents a bibliometric review of fisheries management models in the Mediterranean from 1992 to 2024, with the aim of assessing progress and identifying research gaps. Key countries were analyzed for their contributions, while emerging trends were explored through keyword analysis. The review covered 878 documents, highlighting the variety of models used to assess ecological impacts on Mediterranean fisheries. In particular, the “Assessment for All” (a4a) model emerged as the most widespread, used in 23% of studies, demonstrating its acceptance by researchers. Within the Stock Assessment Models category, a4a was followed by SPiCT and XSA, which were also frequently applied, reflecting their relevance and adaptability in data‐limited and data‐rich fisheries contexts. In the Ecosystem Models category, Ecopath with Ecosim (EwE) was the most utilized tool, widely applied for representing trophic interactions and evaluating ecosystem‐based management scenarios. MaxEnt led in the Species Distribution Models (SDMs) category, valued for its predictive performance using environmental data. Although specific names were often not reported, economic models were also commonly used, indicating the growing incorporation of socio‐economic dimensions in fisheries research. ISIS‐Fish was the most employed within the Population Dynamics Models, allowing detailed simulation and assessment of the impact of different management strategies on fisheries, fleets and ecosystems. In the Statistical Models category, Generalized Additive Models (GAMs) dominated, appreciated for their flexibility in modeling non‐linear relationships. Lastly, the Princeton Ocean Model (POM) was the most frequently used in Hydrodynamic and Biogeochemical Models, highlighting its capacity to simulate physical and ecological marine processes.

Expansion of conservation areas should be informed by sectoral interlinkages - Martin Jung; Marta Coll; Anna Metaxas; Stephanie Margarete Thomas; Kazuaki Tsuchiya; Bruno Meirelles de Oliveira; Alexander Popp; Mark Rounsevell (Trends in Ecology & Evolution, 2025)

Understanding the role of biological, environmental and human-impact factors on mercury concentrations in a demersal mesopredator shark - Elena Lloret-Lloret; Ana Fernández; Joan Navarro; Andrea G. Bravo; Carolina Sanpera; Antonio Esteban; José María Bellido; Marta Coll; Joan Giménez (Marine Pollution Bulletin, 2025)

New Fishing Strategies to Face Climate Change Effects on the Spanish Tropical Tuna Fisheries Off Indian Ocean - José Carlos Báez; Ivone A. Czerwinski; María Lourdes Ramos; José María Bellido; Marta Coll (Fisheries Oceanography, 2025)
Tropical tunas, including yellowfin ( Thunnus albacares ), are recognized as a crucial contributor to global food security. Moreover, yellowfin tuna is the most commercially valuable tropical tuna. The Spanish purse seine freezer fleet, actively operating in the Indian Ocean, emerges as a leading contributor to the global yellowfin tuna catch. Currently, the planet is undergoing a climate change, which is poised to alter habitats on a global scale, particularly impacting tropical regions by causing an increase in sea surface temperatures at an unprecedented rate as well as ocean deoxygenation. Consequently, it is foreseeable that large pelagic highly migratory species like tunas may shift their distribution areas, resulting in the translocation of the current fishing grounds. In this context, the main goal of this work is to study the potential shifts of the Spanish purse seine fishing grounds targeting yellowfin tuna within the tropical belt in the Indian Ocean. Our findings suggest that although the largest yellowfin tuna catches have moved northward in latitude, most of the fishing effort, indicated by the greater number of fishing sets, has been located toward the equatorial region. Present results can only be interpreted from a human perspective and following a commercial strategy in response to the management of yellowfin tuna. Therefore, according to the 38 years of the analyzed dataset, a shift in fleet dynamics is apparent. However, we suggest that this new fishing strategy could be not so much attributed to the movement of free schools toward higher latitudes but to complex trade‐off strategies.

Long-term trophic ecology of juvenile Atlantic bluefin tuna in the western mediterranean sea - Mar Pardo; Fernando Á. Fernández-Álvarez; José Luis Varela; Joan Navarro; Antonio Medina; María José Gómez-Vives; Valerio Sbragaglia; Jose María Bellido; Marta Coll; Joan Giménez (Estuarine, Coastal and Shelf Science, 2025)

Cumulative Extreme Events Threaten Penguin Habitats Across the Southern Hemisphere - Míriam Gimeno; Francisco Ramírez; Marta Coll; Andre Chiaradia; Camila Artana (Global Change Biology, 2025)
Upon the rise in the intensity, duration and frequency of extreme events threatening life on Earth across land and ocean, there is a need to select ecologically significant areas for targeted management interventions. This study assesses the spatial overlap of multiple extreme events and calculates the cumulative magnitude faced across the Southern Hemisphere during the last decades, focusing on the 18 species of penguins as ecosystem sentinels that rely on terrestrial and marine environments. Our analysis identifies African, Snares, Emperor, Adélie and Galápagos as the penguin species experiencing the highest cumulative values of extreme events. Additionally, when looking at the trends, we identify that all penguin species, except the Galápagos penguin, will face a potential increase in extreme events if current trends are maintained. This study carries a crucial message in conservation, establishing a spatial framework that allows sounding the alert in ecologically important areas to reduce vulnerability during present and future extreme events.

Fishing activities within Spanish marine protected areas in the Mediterranean Sea - María D. Castro-Cadenas; Martín Barreiros; Maria Bas; Miquel Ortega; Joachim Claudet; Marta Coll; Valerio Sbragaglia (Marine Policy, 2025)

Linking sea and land systems through food web models and value chains: a portrait of the Ebro Delta (NW Mediterranean Sea) - Miquel Ortega; Elena Lloret-Lloret; Marta Coll (Sustainability Science, 2025)
In various parts of the world, the fisheries sector is undergoing a rapid transition due to a combination of ecological and economic stressors. In this context, there is increasing interest in using integrated ecological–economic tools to support ecosystem-based fisheries practices within a value chain framework, aiming to reduce ecological impacts while ensuring socioeconomic benefits. Our study integrates a food web model with a value chain model for an area of the Mediterranean Sea. This case study may provide valuable insights for decision-makers: (1) it allows the calculation of indicators that go beyond the evaluation of species and fisheries incomes, which are relevant for assessing fisheries management; (2) it offers a more comprehensive perspective on what should be considered priority fisheries species and their key characteristics; and (3) it supports the identification of key actors of the fisheries value chain and generates pertinent information to use in vertically integrated decision-making initiatives.

Corrigendum to “Assessing juvenile swordfish (Xiphias gladius) diet as an indicator of marine ecosystem changes in the northwestern Mediterranean Sea” [Mar. Environ. Res. 192 (2023) 106190] - Elena Fernández-Corredor; Luca Francotte; Ilaria Martino; Fernando Á. Fernández-Álvarez; Salvador García-Barcelona; David Macías; Marta Coll; Francisco Ramírez; Joan Navarro; Joan Giménez (Marine Environmental Research, 2025)

Ocean Warming Effects on Catch and Revenue Composition in the Northwestern Mediterranean Sea - Lucía Espasandín; Francisco Ramírez; Miquel Ortega; Ernesto Villarino; Guillem Chust; Valerio Sbragaglia; Marta Coll (Global Change Biology, 2025)
Climate change‐induced ocean warming can have profound implications for marine ecosystems and the socioeconomic activities dependent on them, affecting the catch composition, and fisheries revenue. Our study evaluates spatio‐temporal changes in the Northwestern Mediterranean marine fisheries catch and revenue composition tied to ocean warming and disentangles the different underlying processes. To do so, we analyzed the weighted mean thermal affinity of the catch (Mean Temperature of the Catch: MTC) and revenue (Mean Temperature of Revenue: MTR) across different taxonomic groups, fishing fleets, and fishing harbors, using a 23‐year time series of commercial landings. Results revealed changes in catch and revenue composition, with an overall temporal increase in the MTC (0.68°C per decade) and MTR (0.58°C per decade) linked to local sea temperature. The temporal increase in both indices prevailed across fishing fleets and taxonomic groups. The processes underpinning these changes over time were tropicalization (i.e. relative increase of warm‐affinity species; 41.97% for MTC and 45.20% for MTR), and deborealization (i.e. relative decrease of cold‐affinity species; 46.58% for MTC and 44.99% for MTR), with variability across dimensions. Deborealization particularly influenced pelagic fisheries (i.e. purse‐seiners and surface longliners) and some commercially important species (e.g. European hake, blue whiting, and Norway lobster). Even if the temporal increase in MTC and MTR was consistent across taxonomic groups and fleets, the spatial dimension showed heterogeneity and temporal declines in some cases. In summary, our study provides valuable information about temporal changes in catch composition associated with local ocean warming and reveals potential cascading effects through the social‐ecological system. In particular, we presented the MTR approach for the first time, evidencing ocean warming effects on revenue composition. We suggest that the correlation between changes in catch and revenue composition reveals the adaptive capacity, or fragility of specific fishing fleets and points to management priorities.

The projected impacts of climate change and fishing pressure on a tropical marine food web - Ronaldo Angelini; Maria Alice Leite Lima; Alex Souza Lira; Flávia Lucena-Frédou; Thierry Frédou; Arnaud Bertrand; Tommaso Giarrizzo; Jeroen Steenbeek; Marta Coll; Friedrich Wolfgang Keppeler (Marine Environmental Research, 2025)

Potential Spatial Mismatches Between Marine Predators and Their Prey in the Southern Hemisphere in Response to Climate Change - Maria Bas; Jazel Ouled‐Cheikh; Alba Fuster‐Alonso; Laura Julià; David March; Francisco Ramírez; Luis Cardona; Marta Coll (Global Change Biology, 2025)
Global change is rapidly reshaping species' habitat suitability ranges, hence leading to significant shifts in the distribution of marine life. Contrasting distributional responses among species can alter the spatial overlap between predators and prey, potentially disrupting trophic interactions and affecting food web dynamics. Here, we evaluate long‐term changes in the spatial overlap of habitat suitability ranges for trophically related species, including crustaceans, fish, penguins, and pinnipeds across 12 Large Marine Ecosystems from the Southern Hemisphere, merged into three primary regions: South America, Southern Africa, Australia and New Zealand. To this aim, we first use Boosted Regression Trees (BRTs) to hindcast and project species‐specific changes in suitable habitat from 1850 to 2100 under two future climate scenarios: SSP1‐2.6 (low climate forcing) and SSP5‐8.5 (high climate forcing). We then analyze changes in species habitat suitability and potential predator–prey spatial overlaps. Findings reveal that marine species generally exhibit changes in their suitable habitats, with pronounced shifts towards higher latitudes under the SSP5‐8.5 scenario. However, contrasting trends emerge among predators across functional groups and regions of South America, Southern Africa, Australia and New Zealand. These variations highlight the need for species and regional‐specific management responses. We also project contrasting spatial mismatches between predators and prey: predators experiencing declines in suitable habitat tend to exhibit greater overlap with their prey in future scenarios, whereas those with expanding suitable habitat show reduced spatial overlap with their prey. This study provides valuable insights that can inform spatial management strategies in response to climate change and illustrate how climate change may weaken species' ability to adapt to climate‐driven environmental changes due to trophic disruptions.

Past, present and future of small-pelagic fisheries in the north-western Mediterranean Sea through fishers’ perceptions - Miquel Ortega; Sara Mohamed Santamaria; Christos Zografos; Yesmina Mascarell-Rocher; Marta Coll; Valerio Sbragaglia (Marine Policy, 2025)

Impacts of the COVID-19 pandemic on the Spanish seafood sector - Sebastian Villasante; Arantza Murillas; Pablo Pita; Ana Tubío; Jose J. Pascual-Fernández; Guillherme Arangao; Joan Moranta; Marta Coll; Andrés Ospina-Alvarez; Silvia de Juan; Ana Ruiz-Frau; Raul Prellezo; et al. (Marine Policy, 2024)

Spatiotemporal patterns of public attention to invasive species across an invasion front: a case study of lionfish (Pterois miles) from the Mediterranean Sea - Lara Fazzari; Reut Vardi; Ivan Jaric; Ricardo A. Correia; Marta Coll; Valerio Sbragaglia (Biological Invasions, 2024)
Understanding societal interest in invasive species is crucial as greater public attention can support the success of conservation efforts. One of the main challenges in monitoring societal interest to support conservation is the absence of near-real-time indicators to track large-scale spatiotemporal dynamics of public attention. However, the digital revolution has opened up new opportunities to develop such indicators in support of invasive species research and management. Here, we aim to evaluate public awareness and interest in the invasive lionfish ( Pterois miles ) in the Mediterranean Sea and investigate spatiotemporal patterns of public interest in the species along its invasion front by using Google search volumes as a proxy for public attention. We implemented topic searches for the lionfish to download Google search volumes from 2013 to 2022 and used these data to test two hypotheses: (1) countries experiencing lionfish invasion exhibit higher public attention than those without lionfish, and (2) in invaded countries, public attention peaks around the arrival year, followed by a decline to baseline levels. Our study confirmed the first hypothesis, showing higher public attention in invaded countries. However, temporal patterns of attention did not fully align with the year of lionfish arrival, suggesting that the socio-political complexity of the region (e.g., cultural trends or internet accessibility), may be a key aspect to consider in future studies. Overall our study shows that digital data sources provide a unique opportunity to monitor social aspects of biological invasions with low associated costs and quick access to a great amount of data generated by internet users.

Fish and tips: Historical and projected changes in commercial fish species' habitat suitability in the Southern Hemisphere - Maria Bas; Jazel Ouled-Cheikh; Laura Julià; Alba Fuster-Alonso; David March; Francisco Ramírez; Luis Cardona; Marta Coll (Science of The Total Environment, 2024)

Microplastic characterization in the stomachs of swordfish (Xiphias gladius) from the western Mediterranean Sea - Marco Torresi; Joan Giménez; Joan Navarro; Marta Coll; Salvador García-Barcelona; David Macías; Asunción Borrell; Odei Garcia-Garin (Marine Pollution Bulletin, 2024)

Diversity, competition and collaboration in the Catalan Mediterranean coastal fisheries - Miquel Ortega; Elena Lloret-Lloret; Marta Coll (Ocean & Coastal Management, 2024)

Top predator status and trends: ecological implications, monitoring and mitigation strategies to promote ecosystem-based management - Caterina Maria Fortuna; Tomaso Fortibuoni; Juan Bueno-Pardo; Marta Coll; Anita Franco; Joan Giménez; Yolanda Stranga; Myron A. Peck; Cristina Claver; Sophie Brasseur; Elena Fernández-Corredor; Simonetta Fraschetti; et al. (Frontiers in Marine Science, 2024)
The conservation and management of marine ecosystems hinge on a comprehensive understanding of the status and trends of top predators. This review delves into the ecological significance of marine top predators, examining their roles in maintaining ecosystem stability and functioning through an integrated analysis of current scientific literature. We first assess the efficacy of various monitoring methods, ranging from traditional field observations to cutting-edge technologies like satellite tracking and environmental DNA (eDNA) analysis and evaluating their strengths and limitations in terms of accuracy, spatial coverage, and cost-effectiveness, providing resource managers with essential insights for informed decision-making. Then, by synthesizing data from diverse marine ecosystems, this study offers a comprehensive overview of the trends affecting top predator populations worldwide. We explore the multifaceted impacts of human activities, climate change, and habitat degradation on the abundance and distribution of these key species. In doing so, we shed light on the broader implications of declining top predator populations, such as trophic cascades and altered community structures. Following a thorough assessment of successful strategies for reversing the decline of top predators, a compilation of recommendations is presented, encompassing effective governance interventions. A crucial aspect of effective ecosystem-based management is the implementation of robust monitoring strategies. Mitigation measures are imperative to reverse the adverse impacts on marine top predators. We present a comprehensive array of mitigation options based on successful case studies. These include the establishment of marine protected areas, the enforcement of fisheries regulations, and the promotion of sustainable fishing practices. We deepen the synergies between these strategies and their potential to mitigate human-induced stressors on top predator populations to safeguard their pivotal role in maintaining marine ecosystem structure and function. By examining marine top predators’ ecological significance, analyzing population trends, discussing monitoring techniques, and outlining effective mitigation strategies, we provide a comprehensive resource for researchers, policymakers, and stakeholders engaged in fostering ecosystem-based management approaches. We conclude that integrating these insights into current management frameworks will be essential to safeguard both top predators and the broader marine environment for future generations.

Understanding the response of the Western Mediterranean cephalopods to environment and fishing in a context of alleged winners of change - Carlos Veloy; Marta Coll; Maria Grazia Pennino; Encarnación Garcia; Antonio Esteban; Cristina García-Ruiz; Gregoire Certain; Sandrine Vaz; Angélique Jadaud; María González; Manuel Hidalgo (Marine Environmental Research, 2024)

Trophic level, niche width, and site fidelity of Moroccan forage fish in two contrasting upwelling systems - Hicham Masski; Joan Giménez; Renaud de Stephanis; Marta Coll; Soukaina Ragmane; Souad Abdellaoui; Imane Tai (Estuarine, Coastal and Shelf Science, 2024)

Spatial patterns of β-diversity under cumulative pressures in the Western Mediterranean Sea - M. Grazia Pennino; Juan Pablo Zurano; Manuel Hidalgo; Antonio Esteban; Carlos Veloy; José M. Bellido; Marta Coll (Marine Environmental Research, 2024)

An overview of the ecological roles of Mediterranean chondrichthyans through extinction scenarios - Elena Fernández-Corredor; Jazel Ouled-Cheikh; Joan Navarro; Marta Coll (Reviews in Fish Biology and Fisheries, 2024)
Fisheries, climate change, and habitat degradation are triggering the depletion of marine animal populations worldwide. The ecological impacts of the extinction of keystone species such as chondrichthyans can be far-reaching along the entire food web. Here, we first reviewed the trophic ecology of the 81 chondrichthyan species of the Mediterranean Sea through a literature search. We then compared prey composition among chondrichthyan species considering their taxonomic group, body size, and habitat. Finally, we represented the Mediterranean meta-web, emphasizing the chondrichthyan groups, using a qualitative network approach, and tested the vulnerability of the food web to selective removals of threatened chondrichthyan species by applying different extinction scenarios. We found trophic data for 53 species, which highlights the need to complement current knowledge gaps for many species. Diet dissimilarities between chondrichthyan taxa were detected, mainly due to the consumption of crustaceans and cephalopods. We found that large chondrichthyan species had a major contribution to the trophic dissimilarity and the omnivory of the food web when compared to small and medium-sized species. Conservation efforts within the Mediterranean chondrichthyan community may be particularly important for this group, as high levels of omnivory could moderate the occurrence of trophic cascades, while high trophic similarity can lead to less diverse ecosystems. This study provides a first overview of the ecological role of chondrichthyans in the Mediterranean and highlights the urgent research needed to increase the knowledge about these key species in the Mediterranean marine food web.

Changes in cardiovascular health and white matter integrity with aerobic exercise, cognitive and combined training in physically inactive healthy late-middle-aged adults: the “Projecte Moviment” randomized controlled trial - Francesca Roig-Coll; Alba Castells-Sánchez; Gemma Monté-Rubio; Rosalía Dacosta-Aguayo; Noemí Lamonja-Vicente; Pere Torán-Monserrat; Guillem Pere; Alberto García-Molina; José Maria Tormos; Maria Teresa Alzamora; Dimitriadis Stavros; Marta Sánchez-Ceron; et al. (European Journal of Applied Physiology, 2024)
Introduction This is a 12-weeks randomized controlled trial examining the effects of aerobic exercise (AE), computerized cognitive training (CCT) and their combination (COMB). We aim to investigate their impact on cardiovascular health and white matter (WM) integrity and how they contribute to the cognitive benefits. Methods 109 participants were recruited and 82 (62% female; age = 58.38 ± 5.47) finished the intervention with > 80% adherence. We report changes in cardiovascular risk factors and WM integrity (fractional anisotropy (FA); mean diffusivity (MD)), how they might be related to changes in physical activity, age and sex, and their potential role as mediators in cognitive improvements. Results A decrease in BMI (SMD = − 0.32, p = 0.039), waist circumference (SMD = − 0.42, p = 0.003) and diastolic blood pressure (DBP) (SMD = − 0.42, p = 0.006) in the AE group and a decrease in BMI (SMD = − 0.34, p = 0.031) and DBP (SMD = − 0.32, p = 0.034) in the COMB group compared to the waitlist control group was observed. We also found decreased global MD in the CCT group (SMD = − 0.34; p = 0.032) and significant intervention-related changes in FA and MD in the frontal and temporal lobes in the COMB group. Conclusions We found changes in anthropometric measures that suggest initial benefits on cardiovascular health after only 12 weeks of AE and changes in WM microstructure in the CCT and COMB groups. These results add evidence of the clinical relevance of lifestyle interventions and the potential benefits when combining them. Clinical Trial Registration ClinicalTrials.gov NCT031123900.

Future climate‐induced distribution shifts in a sexually dimorphic key predator of the Southern Ocean - Jazel Ouled‐Cheikh; David March; Renato Borras‐Chavez; Massimiliano Drago; Michael E. Goebel; José M. Fariña; Manel Gazo; Marta Coll; Luis Cardona (Global Change Biology, 2024)
The response to climate change in highly dimorphic species can be hindered by differences between sexes in habitat preferences and movement patterns. The Antarctic fur seal, Arctocephalus gazella , is the most abundant pinniped in the Southern Hemisphere, and one of the main consumers of Antarctic krill, Euphausia superba , in the Southern Ocean. However, the populations breeding in the Atlantic Southern Ocean are decreasing, partly due to global warming. Male and female Antarctic fur seals differ greatly in body size and foraging ecology, and little is known about their sex‐specific responses to climate change. We used satellite tracking data and Earth System Models to predict changes in habitat suitability for male and female Antarctic fur seals from the Western Antarctic Peninsula under different climate change scenarios. Under the most extreme scenario (SSP5‐8.5; global average temperature +4.4°C projected by 2100), suitable habitat patches will shift southward during the non‐breeding season, leading to a minor overall habitat loss. The impact will be more pronounced for females than for males. The reduction of winter foraging grounds might decrease the survival of post‐weaned females, reducing recruitment and jeopardizing population viability. During the breeding season, when males fast on land, suitable foraging grounds for females off the South Shetland Islands will remain largely unmodified, and new ones will emerge in the Bellingshausen Sea. As Antarctic fur seals are income breeders, the foraging grounds of females should be reasonably close to the breeding colony. As a result, the new suitable foraging grounds will be useful for females only if nearby beaches currently covered by sea ice emerge by the end of the century. Furthermore, the colonization of these new, ice‐free breeding locations might be limited by strong female philopatry. These results should be considered when managing the fisheries of Antarctic krill in the Southern Ocean.

Assessing mercury contamination in Southern Hemisphere marine ecosystems: The role of penguins as effective bioindicators - Míriam Gimeno; Laia Rossell; Laura Julià; Joan Giménez; Carolina Sanpera; Marta Coll; Paco Bustamante; Francisco Ramírez (Environmental Pollution, 2024)

Retrospective analysis of the pelagic ecosystem of the Western Mediterranean Sea: Drivers, changes and effects - Marta Coll; José María Bellido; Maria Grazia Pennino; Marta Albo-Puigserver; José Carlos Báez; Villy Christensen; Xavier Corrales; Elena Fernández-Corredor; Joan Giménez; Laura Julià; Elena Lloret-Lloret; Diego Macias; et al. (Science of The Total Environment, 2024)

Climate and human stressors on global penguin hotspots: Current assessments for future conservation - Míriam Gimeno; Joan Giménez; Andre Chiaradia; Lloyd S. Davis; Philip J. Seddon; Yan Ropert‐Coudert; Ryan R. Reisinger; Marta Coll; Francisco Ramírez (Global Change Biology, 2024)
As charismatic and iconic species, penguins can act as “ambassadors” or flagship species to promote the conservation of marine habitats in the Southern Hemisphere. Unfortunately, there is a lack of reliable, comprehensive, and systematic analysis aimed at compiling spatially explicit assessments of the multiple impacts that the world's 18 species of penguin are facing. We provide such an assessment by combining the available penguin occurrence information from Global Biodiversity Information Facility (>800,000 occurrences) with three main stressors: climate‐driven environmental changes at sea, industrial fisheries, and human disturbances on land. Our analyses provide a quantitative assessment of how these impacts are unevenly distributed spatially within species' distribution ranges. Consequently, contrasting pressures are expected among species, and populations within species. The areas coinciding with the greatest impacts for penguins are the coast of Perú, the Patagonian Shelf, the Benguela upwelling region, and the Australian and New Zealand coasts. When weighting these potential stressors with species‐specific vulnerabilities, Humboldt ( Spheniscus humboldti ), African ( Spheniscus demersus ), and Chinstrap penguin ( Pygoscelis antarcticus ) emerge as the species under the most pressure. Our approach explicitly differentiates between climate and human stressors, since the more achievable management of local anthropogenic stressors (e.g., fisheries and land‐based threats) may provide a suitable means for facilitating cumulative impacts on penguins, especially where they may remain resilient to global processes such as climate change. Moreover, our study highlights some poorly represented species such as the Northern Rockhopper ( Eudyptes moseleyi ), Snares ( Eudyptes robustus ), and Erect‐crested penguin ( Eudyptes sclateri ) that need internationally coordinated efforts for data acquisition and data sharing to understand their spatial distribution properly.

Contribution of area-based fisheries management measures to fisheries sustainability and marine conservation: a global scoping review - Dimitra Petza; Panagiotis Anastopoulos; Stefanos Kalogirou; Marta Coll; Serge Garcia; Michel Kaiser; Nikoletta Koukourouvli; Irene Lourdi; Jake Rice; Marija Sciberras; Stelios Katsanevakis (Reviews in Fish Biology and Fisheries, 2023)
Area-based fisheries management measures (ABFMs) are commonly related to the sustainable use of resources but are increasingly considered broader conservation measures. This Scoping Review (ScR) identified and mapped the evidence base regarding the contribution of ABFMs to fisheries sustainability and marine conservation. The ScR was conducted following the JBI methodology and the PRISMA statement. A total of 2,391 documents were identified, and following a two-stage screening process, 151 documents were eventually included in the ScR for full review and data extraction. Most of the documents were published during the last 12 years. Studies had a wide geographical distribution (mainly located in Europe and North America), were primarily conducted at the subnational level, concerned fishing restrictions of towed gears, and assessed ABFMs from a single stock’s perspective. ABFMs identified were of various types, and the use of terminology was not consistent in the literature. Multiple combinations of data collection (primarily experimental surveys/sampling and open data sources) and analysis methods (most commonly, fisheries and ecological analyses and modelling) were applied (often in combination), using a variety of different metrics. Various knowledge gaps emerged, mainly related to the study of ABFMs networks and the application of an interdisciplinary and ecosystem-based approach for assessing ABFMs. The social, economic, and environmental impact of ABFMs was positive in most cases (56%) and in less cases negative (22%) or mixed (14%). This ScR is a valuable source of information for the contribution of ABFMs to rebuilding marine ecosystems and attaining CBD conservation targets through the lens of the OECM concept. Graphical abstract

Identifying and prioritizing demersal fisheries restricted areas based on combined ecological and fisheries criteria: The western Mediterranean - Miquel Ortega; María D. Castro-Cadenas; Jeroen Steenbeek; Marta Coll (Marine Policy, 2023)

Assessing juvenile swordfish (Xiphias gladius) diet as an indicator of marine ecosystem changes in the northwestern Mediterranean Sea - Elena Fernández-Corredor; Luca Francotte; Ilaria Martino; Fernando Á. Fernández-Álvarez; Salvador García-Barcelona; David Macías; Marta Coll; Francisco Ramírez; Joan Navarro; Joan Giménez (Marine Environmental Research, 2023)

Automatic silo axis detection from RGB-D sensor data for content monitoring - Oriol Vila; Imma Boada; Narcis Coll; Marta Fort; Esteve Farres (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Sowing potential transformative changes in the fishing and agrifood systems – Conference report - Joan Moranta; David Florido-del-Corral; Lucía López-López; Sílvia Gómez; Julio Agujetas; Marta Albo-Puigserver; Zoe W. Brent; Lamine Bathily; Rita Calvário; Marta Cavallé; Marta Coll; Annya Crane; et al. (Marine Policy, 2023)

Evaluation of fisheries management policies in the alien species-rich Eastern Mediterranean under climate change - Eyal Ofir; Xavier Corrales; Marta Coll; Johanna Jacomina Heymans; Menachem Goren; Jeroen Steenbeek; Yael Amitai; Noam Shachar; Gideon Gal (Frontiers in Marine Science, 2023)
Recent decades have witnessed declines in the amount of fishing catch due to changes in the marine ecosystem of the Eastern Mediterranean Sea. These changes are mainly a consequence of direct human activities as well as global warming and the entry of invasive species. Therefore, there is a need to improve fisheries management so that it accounts for the various stressors and uses of the marine environment beyond fishing, while providing sustainable catches and maintaining a healthy ecosystem. The ability to understand, and sustainably manage, the fishing industry relies on models capable of analyzing and predicting the effects of fishing on the entire ecosystem. In this study, we apply Ecospace, the spatial-temporal component of the Ecopath with Ecosim approach, to study the Israeli continental shelf to evaluate the impact of climate change and alternative management options on the ecosystem. We examine several management alternatives under the severe assumption of the RCP8.5 climate change scenario for the region. Results indicate that under business-as-usual conditions, the biomass of the native species will decrease, the biomass of the invasive species will increase, and there will be a decrease in the fishing catch. In addition, of the management alternatives examined, the alternative of prohibition of fishing in the northern region of Israel along with the establishment of a network of marine nature reserves provides the optimal response for the ecosystem and fisheries. The Achziv Nature Reserve is projected to be successful, improving the biomass of local species and reducing, to some extent, the presence of invasive species. These results are consistent with visual surveys conducted inside and outside the reserve by the Israeli Nature and Parks Authority. Furthermore, simulation results indicate spill-over effects in areas close to nature reserves yielding higher catches in those regions.

Trophic structure and fishing impacts on an oligotrophic ecosystem in the Western Mediterranean: the Balearic Islands - Paula Sánchez-Zulueta; María Valls; Beatriz Guijarro; María Ángeles Torres; María Ángeles Zapata; Marta Coll; Xavier Corrales; Eider Andonegi; Marta Díaz-Valdés; Enric Massutí; Francesc Ordines (Frontiers in Marine Science, 2023)
Within the context of the ecosystem approach to fisheries management, an ecosystem model was developed for the Balearic Islands in the early 2000s, covering from 0 to 800 m of depth. The aim of the study was to describe the structure and functioning of the ecosystem together with the fishing impacts. The results show that the biomass of the primary producers (PP), mainly dominated by Posidonia oceanica meadows and red algae beds, represented a high percentage of the biomass (39.20%) in the ecosystem. Most of the trophic flows occurred between PP (mostly benthic) and trophic level II. The mixed trophic impact analysis also highlighted a positive impact of the functional groups (FGs) at the base of the food web. Besides, there were important trophic flows between several demersal FGs, and many groups of the pelagic compartment, confirming the importance of the benthopelagic coupling previously reported. The mean trophic level of the catch (mTLc=2.76) was lower than those reported in adjacent areas due to the discard of benthic producers. By excluding benthic PP, the Balearic Islands showed the highest mTLc (3.44) among all the Mediterranean areas modelled, probably due to differences in the trophic structure, lower fisheries exploitation levels and lower development of the purse seine fleet targeting small pelagic fishes. The mean transfer efficiency (21.80%) was double than the global average (10%), which highlights the oligotrophy of the system, the importance of demersal production which has lower rates of transfer through the food web, and a more efficient use of nutrients in the ecosystem. Sponges, one of the most important groups of benthic invertebrates in the Balearic Archipelago, are known to recycle dissolved organic matter, which is reintroduced into the food web similar to the microbial loop, but the magnitude of this and other processes remains still unknown in this area. The present study is a first step to develop spatio-temporal simulations under different exploitation scenarios and to calculate ecological indicators to assess the state of the marine environment in this region.

Making protected areas effective for biodiversity, climate and food - Almut Arneth; Paul Leadley; Joachim Claudet; Marta Coll; Carlo Rondinini; Mark D. A. Rounsevell; Yunne‐Jai Shin; Peter Alexander; Richard Fuchs (Global Change Biology, 2023)
The spatial extent of marine and terrestrial protected areas (PAs) was among the most intensely debated issues prior to the decision about the post‐2020 Global Biodiversity Framework (GBF) of the Convention on Biological Diversity. Positive impacts of PAs on habitats, species diversity and abundance are well documented. Yet, biodiversity loss continues unabated despite efforts to protect 17% of land and 10% of the oceans by 2020. This casts doubt on whether extending PAs to 30%, the agreed target in the Kunming‐Montreal GBF, will indeed achieve meaningful biodiversity benefits. Critically, the focus on area coverage obscures the importance of PA effectiveness and overlooks concerns about the impact of PAs on other sustainability objectives. We propose a simple means of assessing and visualising the complex relationships between PA area coverage and effectiveness and their effects on biodiversity conservation, nature‐based climate mitigation and food production. Our analysis illustrates how achieving a 30% PA global target could be beneficial for biodiversity and climate. It also highlights important caveats: (i) achieving lofty area coverage objectives alone will be of little benefit without concomitant improvements in effectiveness, (ii) trade‐offs with food production particularly for high levels of coverage and effectiveness are likely and (iii) important differences in terrestrial and marine systems need to be recognized when setting and implementing PA targets. The CBD's call for a significant increase in PA will need to be accompanied by clear PA effectiveness goals to reduce and revert dangerous anthropogenic impacts on socio‐ecological systems and biodiversity.

Sardines at a junction: Seascape genomics reveals ecological and oceanographic drivers of variation in the NW Mediterranean Sea - Aglaia Antoniou; Tereza Manousaki; Francisco Ramírez; Alessia Cariani; Rita Cannas; Panagiotis Kasapidis; Antonios Magoulas; Marta Albo‐Puigserver; Elena Lloret‐Lloret; Jose Maria Bellido; Maria Grazia Pennino; Maria Cristina Follesa; et al. (Molecular Ecology, 2023)
By evaluating genetic variation across the entire genome, one can address existing questions in a novel way while raising new ones. The latter includes how different local environments influence adaptive and neutral genomic variation within and among populations, providing insights into local adaptation of natural populations and their responses to global change. Here, under a seascape genomic approach, ddRAD data of 4609 single nucleotide polymorphisms (SNPs) from 398 sardines ( Sardina pilchardus ) collected in 11 Mediterranean and one Atlantic site were generated. These were used along with oceanographic and ecological information to detect signals of adaptive divergence with gene flow across environmental gradients. The studied sardines constitute two clusters ( F ST = 0.07), a pattern attributed to outlier loci, highlighting putative local adaptation. The trend in the number of days with sea surface temperature above 19°C, a critical threshold for successful sardine spawning, was crucial at all levels of population structuring with implications on the species' key biological processes. Outliers link candidate SNPs to the region's environmental heterogeneity. Our findings provide evidence for a dynamic equilibrium in which population structure is maintained by physical and ecological factors under the opposing influences of migration and selection. This dynamic in a natural system warrants continuous monitoring under a seascape genomic approach that might benefit from a temporal and more detailed spatial dimension. Our results may contribute to complementary studies aimed at providing deeper insights into the mechanistic processes underlying population structuring. Those are key to understanding and predicting future changes and responses of this highly exploited species in the face of climate change.

Modelling seabirds biodiversity through Bayesian Spatial Beta regression models: A proxy to inform marine protected areas in the Mediterranean Sea - Blanca Sarzo; Joaquín Martínez-Minaya; Maria Grazia Pennino; David Conesa; Marta Coll (Marine Environmental Research, 2023)

Correction: New approaches to old problems: how to introduce ecosystem information into modern fisheries management advice - Maria Grazia Pennino; Jennifer Rehren; Amina Tifoura; Davinia Lojo; Marta Coll (Hydrobiologia, 2023)

New approaches to old problems: how to introduce ecosystem information into modern fisheries management advice - Maria Grazia Pennino; Jennifer Rehren; Amina Tifoura; Davinia Lojo; Marta Coll (Hydrobiologia, 2023)

Understanding the role of ecological factors affecting mercury concentrations in the blue shark (Prionace glauca) - Lola Riesgo; Carola Sanpera; Salvador García-Barcelona; Moisès Sánchez-Fortún; Marta Coll; Joan Navarro (Chemosphere, 2023)

Differential effect of fisheries to the COVID-19 pandemic in the region of Andalusia (Spain) - Marta Cousido-Rocha; Marta González Carballo; Maria Grazia Pennino; Marta Coll; José C. Báez (Marine Policy, 2023)

Tree species growth response to climate in mixtures of Quercus robur/Quercus petraea and Pinus sylvestris across Europe - a dynamic, sensitive equilibrium - Sonja Vospernik; Michael Heym; Hans Pretzsch; Maciej Pach; Mathias Steckel; Jorge Aldea; Gediminas Brazaitis; Andrés Bravo-Oviedo; Miren Del Rio; Magnus Löf; Marta Pardos; Kamil Bielak; et al. (Forest Ecology and Management, 2023)

The relative importance of biological and environmental factors on the trophodynamics of a pelagic marine predator, the blue shark (Prionace glauca) - Alba Vidal; Laura Cardador; Salvador Garcia-Barcelona; David Macias; Jean-Noel Druon; Marta Coll; Joan Navarro (Marine Environmental Research, 2023)

Climate and fishing simultaneously impact small pelagic fish in the oceans around the southernmost tip of Africa - Francisco Ramírez; Lynne J. Shannon; Carl D. van der Lingen; Laura Julià; Jeroen Steenbeek; Marta Coll (Frontiers in Marine Science, 2022)
Climate and fisheries interact, often synergistically, and may challenge marine ecosystem functioning and, ultimately, seafood provision and human wellbeing that depend on them. Holistic and integrative approaches aiming at evaluating the spatial overlap between these major stressors are crucial for identifying marine regions and key fish species that require conservation priority to prevent possible future collapses. Based on highly resolved information on environmental conditions and fishing pressure from the Southern Benguela and the Agulhas Bank ecosystems off South Africa, we identified the main areas where small pelagic fish species (European anchovy Engraulis encrasicolus , Pacific sardine Sardinops sagax , and West Coast round herring Etrumeus whiteheadi ) have been highly impacted in terms of unfavourable environmental conditions and fishing pressure over the period 1993-2018. We termed these areas cumulative “hotspots” of climate change and fishing impact. We also identified fishing grounds where environmental conditions are now more favourable for these pelagic fish species, terming these “bright spots” of climate change. Environmental conditions and fishing intensity show contrasting patterns between the Southern Benguela and the Agulhas Bank ecosystems, with the Southern Benguela region accumulating most of the cumulative hotspots and showing the most negative trends in CPUE (a proxy for local fish abundance). Contrastingly, bright spots, identified on the south coast but also south of Cape Town, showed more positive trends in CPUE, suggesting that they may support sustainable growth of the small pelagic fishery in the medium term. Focussing future fishing effort on these bright spots may serve to alleviate pressure on the doubly and highly impacted cumulative hotspots from the western side of the southernmost tip of Africa.

Clinical impact of rare variants associated with inherited channelopathies: a 5-year update - Georgia Sarquella-Brugada; Anna Fernandez-Falgueras; Sergi Cesar; Elena Arbelo; Mónica Coll; Alexandra Perez-Serra; Marta Puigmulé; Anna Iglesias; Mireia Alcalde; Marta Vallverdú-Prats; Victoria Fiol; Carles Ferrer-Costa; et al. (Human Genetics, 2022)
A proper interpretation of the pathogenicity of rare variants is crucial before clinical translation. Ongoing addition of new data may modify previous variant classifications; however, how often a reanalysis is necessary remains undefined. We aimed to extensively reanalyze rare variants associated with inherited channelopathies originally classified 5 years ago and its clinical impact. In 2016, rare variants identified through genetic analysis were classified following the American College of Medical Genetics and Genomics’ recommendations. Five years later, we have reclassified the same variants following the same recommendations but including new available data. Potential clinical implications were discussed. Our cohort included 49 cases of inherited channelopathies diagnosed in 2016. Update show that 18.36% of the variants changed classification mainly due to improved global frequency data. Reclassifications mostly occurred in minority genes associated with channelopathies. Similar percentage of variants remain as deleterious nowadays, located in main known genes ( SCN5A, KCNH2 and KCNQ1 ). In 2016, 69.38% of variants were classified as unknown significance, but now, 53.06% of variants are classified as such, remaining the most common group. No management was modified after translation of genetic data into clinics. After 5 years, nearly 20% of rare variants associated with inherited channelopathies were reclassified. This supports performing periodic reanalyses of no more than 5 years since last classification. Use of newly available data is necessary, especially concerning global frequencies and family segregation. Personalized clinical translation of rare variants can be crucial to management if a significant change in classification is identified.

The current knowledge status of the genetic population structure of the European sardine (Sardina pilchardus): uncertainties to be solved for an appropriate fishery management - Marta Caballero-Huertas; Xènia Frigola-Tepe; Marta Coll; Marta Muñoz; Jordi Viñas (Reviews in Fish Biology and Fisheries, 2022)

Recreational angling and spearfishing on social media: insights on harvesting patterns, social engagement and sentiments related to the distributional range shift of a marine invasive species - Valerio Sbragaglia; Lucía Espasandín; Salvatore Coco; Alberto Felici; Ricardo A. Correia; Marta Coll; Robert Arlinghaus (Reviews in Fish Biology and Fisheries, 2022)

Challenges for Marine Ecological Assessments: Completeness of Findable, Accessible, Interoperable, and Reusable Biodiversity Data in European Seas - Francisco Ramírez; Valerio Sbragaglia; Karen Soacha; Marta Coll; Jaume Piera (Frontiers in Marine Science, 2022)
The ongoing contemporary biodiversity crisis may result in much of ocean’s biodiversity to be lost or deeply modified without even being known. As the climate and anthropogenic-related impacts on marine systems accelerate, biodiversity knowledge integration is urgently required to evaluate and monitor marine ecosystems and to support suitable responses to underpin a sustainable future. The Census of Marine Life (CoML, 2000–2010) was the largest global research program on marine biodiversity. A decade after, and coinciding with the steep increase of digitalization of our society, we review existing findability, accessibility, interoperability, and reusability (FAIR) biodiversity data coming from one of the most reliable online information systems: the Global Biodiversity Information Facility (GBIF). We evaluate the completeness of available datasets with respect to the CoML benchmark, along with progresses in understanding spatial–temporal patterns of marine biodiversity in the European Seas in the last decades. Overall, we observe severe biases in available biodiversity data toward the north-western marine regions (particularly around the United Kingdom and the North Sea), the most recent years (with a peak in the number of reported occurrences in the 2010s) and the most conspicuous, abundant, and likely “appealing” taxa (e.g., crustaceans, echinoderms or fish). These biases may hamper research applications, but also global-scale data needs and integrative assessments required to support cost-effective progresses toward global biodiversity conservation. National to international joint efforts aimed at enhancing data acquisition and mobilization from poorly known regions, periods, and taxa are desirable if we aim to address these potential biases for the effective monitoring of marine ecosystems and the evaluation of ongoing impacts on biogeographic patterns and ecosystem functioning and services.

Mesoscale productivity fronts and local fishing opportunities in the European Seas - Jean‐Noël Druon; Didier Gascuel; Maurizio Gibin; Antonella Zanzi; Jean‐Marc Fromentin; Francesco Colloca; Pierre Hélaouët; Marta Coll; Alessandro Mannini; Joanna K Bluemel; Chiara Piroddi; Francois Bastardie; et al. (Fish and Fisheries, 2021)
This study evaluates the relationship between both commercial and scientific spatial fisheries data and a new satellite‐based estimate of potential fish production (Ocean Productivity available to Fish, OPFish) in the European Seas. To construct OPFish, we used productivity frontal features derived from chlorophyll‐ a horizontal gradients, which characterize 10%–20% of the global phytoplankton production that effectively fuels higher trophic levels. OPFish is relatively consistent with the spatial distribution of both pelagic and demersal fish landings and catches per unit of effort (LPUEs and CPUEs, respectively). An index of harvest relative to ocean productivity (H P index) is calculated by dividing these LPUEs or CPUEs with OPFish. The H P index reflects the intensity of fishing by gear type with regard to local fish production. Low H P levels indicate lower LPUEs or CPUEs than expected from oceanic production, suggesting over‐exploitation, while high H P levels imply more sustainable fishing. H P allows comparing the production‐dependent suitability of local fishing intensities. Our results from bottom trawl data highlight that over‐exploitation of demersal species from the shelves is twice as high in the Mediterranean Sea than in the North‐East Atlantic. The estimate of H P index by dominant pelagic and demersal gears suggests that midwater and bottom otter trawls are associated with the lowest and highest overfishing, respectively. The contrasts of fishing intensity at local scales captured by the H P index suggest that accounting for the local potential fish production can promote fisheries sustainability in the context of ecosystem‐based fisheries management as required by international marine policies.

Where Is More Important Than How in Coastal and Marine Ecosystems Restoration - Simonetta Fraschetti; Chris McOwen; Loredana Papa; Nadia Papadopoulou; Meri Bilan; Christoffer Boström; Pol Capdevila; Marina Carreiro-Silva; Laura Carugati; Emma Cebrian; Marta Coll; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Restoration is considered an effective strategy to accelerate the recovery of biological communities at local scale. However, the effects of restoration actions in the marine ecosystems are still unpredictable. We performed a global analysis of published literature to identify the factors increasing the probability of restoration success in coastal and marine systems. Our results confirm that the majority of active restoration initiatives are still concentrated in the northern hemisphere and that most of information gathered from restoration efforts derives from a relatively small subset of species. The analysis also indicates that many studies are still experimental in nature, covering small spatial and temporal scales. Despite the limits of assessing restoration effectiveness in absence of a standardized definition of success, the context (degree of human impact, ecosystem type, habitat) of where the restoration activity is undertaken is of greater relevance to a successful outcome than how (method) the restoration is carried out. Contrary to expectations, we found that restoration is not necessarily more successful closer to protected areas (PA) and in areas of moderate human impact. This result can be motivated by the limits in assessing the success of interventions and by the tendency of selecting areas in more obvious need of restoration, where the potential of actively restoring a degraded site is more evident. Restoration sites prioritization considering human uses and conservation status present in the region is of vital importance to obtain the intended outcomes and galvanize further actions.

Editorial: Managing for the Future: Challenges and Approaches for Disentangling the Relative Roles of Environmental Change and Fishing in Marine Ecosystems - Alida Bundy; Paul E. Renaud; Marta Coll; Stefan Koenigstein; Susa Niiranen; Maria Grazia Pennino; Jamie C. Tam; Morgane Travers-Trolet (Frontiers in Marine Science, 2021)

Assessment of the Streptomyces-plant system to mitigate the impact of Cr(VI) and lindane in experimental soils - María Zoleica Simón Solá; Carolina Prado; Mariana Rosa; María Victoria Coll Aráoz; Claudia Susana Benimeli; Marta Alejandra Polti; Analia Alvarez (Environmental Science and Pollution Research, 2021)

Changes in Life History Traits of Small Pelagic Fish in the Western Mediterranean Sea - Marta Albo-Puigserver; Maria Grazia Pennino; Jose María Bellido; Ana Isabel Colmenero; Ana Giráldez; Manuel Hidalgo; John Gabriel Ramírez; Jeroen Steenbeek; Pedro Torres; Marta Cousido-Rocha; Marta Coll (Frontiers in Marine Science, 2021)
Small pelagic fish (SPF) in the western Mediterranean Sea are key elements of the marine food web and are important in terms of biomass and fisheries catches. Significant declines in biomass, landings, and changes in the age/size structure of sardine Sardina pilchardus and anchovy Engraulis encrasicolus have been observed in recent decades, particularly in the northern area of the western Mediterranean Sea. To understand the different patterns observed in SPF populations, we analyzed key life history traits [total length at age, length at maturity, gonadosomatic index (GSI), and body condition (Kn)] of sardine and anchovy collected between 2003 and 2017, from different fishing harbors distributed along a latitudinal gradient from northern to southern Spain. We used Generalized Linear Models (GLM) to estimate the length at maturity and Generalized Additive Models (GAMs) to test the relationship with environmental variables (seawater temperature, water currents, and net primary productivity). The life history traits of both species presented seasonal, interannual and latitudinal differences with a clear decline in length at age, length at first maturity, and body condition, for both species in the northern part of the study area. In the southern part, on the contrary, life history traits did not present a clear temporal trend. The environmental conditions partially explained the long-term changes in life history traits, but the selected variables differed between areas, highlighting the importance of regional oceanographic conditions to understand the dynamics of small pelagic fish. The truncated length-at-age pattern for both species with the disappearance of the larger individuals of the population could have contributed to the poor condition of small pelagic fish populations in the northern part of the western Mediterranean Sea in recent years. In the south area, recent declines in body condition for sardine and anchovy were observed and could be a possible first sign for future population declines. This study highlights the importance of understanding the trade-off between the energy invested in reproduction, maintenance and growth at seasonal and interannual level to advance our knowledge on how environmental and human pressures influence population dynamics of small pelagic fish at local and regional scales.

Supporting Spatial Management of Data-Poor, Small-Scale Fisheries With a Bayesian Approach - Jennifer Rehren; Maria Grazia Pennino; Marta Coll; Narriman Jiddawi; Christopher Muhando (Frontiers in Marine Science, 2021)
Marine conservation areas are an important tool for the sustainable management of multispecies, small-scale fisheries. Effective spatial management requires a proper understanding of the spatial distribution of target species and the identification of its environmental drivers. Small-scale fisheries, however, often face scarcity and low-quality of data. In these situations, approaches for the prioritization of conservation areas need to deal with scattered, biased, and short-term information and ideally should quantify data- and model-specific uncertainties for a better understanding of the risks related to management interventions. We used a Bayesian hierarchical species distribution modeling approach on annual landing data of the heavily exploited, small-scale, and data-poor fishery of Chwaka Bay (Zanzibar) in the Western Indian Ocean to understand the distribution of the key target species and identify potential areas for conservation. Few commonalities were found in the set of important habitat and environmental drivers among species, but temperature, depth, and seagrass cover affected the spatial distribution of three of the six analyzed species. A comparison of our results with information from ecological studies suggests that our approach predicts the distribution of the analyzed species reasonably well. Furthermore, the two main common areas of high relative abundance identified in our study have been previously suggested by the local fisher as important areas for spatial conservation. By using short-term, catch per unit of effort data in a Bayesian hierarchical framework, we quantify the associated uncertainties while accounting for spatial dependencies. More importantly, the use of accessible and interpretable tools, such as the here created spatial maps, can frame a better understanding of spatio-temporal management for local fishers. Our approach, thus, supports the operability of spatial management in small-scale fisheries suffering from a general lack of long-term fisheries information and fisheries independent data.

Effects of Nutrient Management Scenarios on Marine Food Webs: A Pan-European Assessment in Support of the Marine Strategy Framework Directive - Chiara Piroddi; Ekin Akoglu; Eider Andonegi; Jacob W. Bentley; Igor Celić; Marta Coll; Donna Dimarchopoulou; René Friedland; Kim de Mutsert; Raphael Girardin; Elisa Garcia-Gorriz; Bruna Grizzetti; et al. (Frontiers in Marine Science, 2021)
Eutrophication is one of the most important anthropogenic pressures impacting coastal seas. In Europe, several legislations and management measures have been implemented to halt nutrient overloading in marine ecosystems. This study evaluates the impact of freshwater nutrient control measures on higher trophic levels (HTL) in European marine ecosystems following descriptors and criteria as defined by the Marine Strategy Framework Directive (MSFD). We used a novel pan-European marine modeling ensemble of fourteen HTL models, covering almost all the EU seas, under two nutrient management scenarios. Results from our projections suggest that the proposed nutrient reduction measures may not have a significant impact on the structure and function of European marine ecosystems. Among the assessed criteria, the spawning stock biomass of commercially important fish stocks and the biomass of small pelagic fishes would be the most impacted, albeit with values lower than 2.5%. For the other criteria/indicators, such as species diversity and trophic level indicators, the impact was lower. The Black Sea and the North-East Atlantic were the most negatively impacted regions, while the Baltic Sea was the only region showing signs of improvement. Coastal and shelf areas were more sensitive to environmental changes than large regional and sub-regional ecosystems that also include open seas. This is the first pan-European multi-model comparison study used to assess the impacts of land-based measures on marine and coastal European ecosystems through a set of selected ecological indicators. Since anthropogenic pressures are expanding apace in the marine environment and policy makers need to use rapid and effective policy measures for fast-changing environments, this modeling framework is an essential asset in supporting and guiding EU policy needs and decisions.

The Seasonal Distribution of a Highly Commercial Fish Is Related to Ontogenetic Changes in Its Feeding Strategy - Elena Lloret-Lloret; Joan Navarro; Joan Giménez; Nieves López; Marta Albo-Puigserver; Maria Grazia Pennino; Marta Coll (Frontiers in Marine Science, 2020)
Improving the knowledge on the biology, ecology and distribution of marine resources exploited by fisheries is necessary to achieve population recovery and sustainable fisheries management. European hake ( Merluccius merluccius ) is one of the most important target species in the Mediterranean Sea and is largely overexploited by industrial fisheries. Here, we used two methodological approaches to further investigate the seasonal variation in the spatial distribution of European hake considering ontogenetic changes and trophic ecology in the western Mediterranean Sea. Our main aim was to explore if spatial changes in hake distribution were related to trophic behavior, in addition to key environmental factors. We employed a hierarchical Bayesian species distribution modeling approach (B-SDM), using spatial data from two oceanographic surveys conducted during winter and summer. We analyzed how the environmental variables, together with abundance and mean weight distribution of the main preys identified for European hake, affected the seasonal distribution of the species. Results revealed clear differences in the distribution of the European hake between seasons, which were indeed partially correlated to the distribution of their main preys, in addition to the environment. Stable isotope values and Bayesian isotopic mixing models (MixSIAR) revealed substantial seasonal and ontogenetic differences in trophic habits of European hake, partly matching the spatial distribution results. These findings could have implications for a future seasonal-based adaptive fisheries management, as local depletion of prey, or variation in size and condition may affect European hake presence in this area. Moreover, this study illustrates how the sequential application of methodologies provides a more holistic understanding of species seasonality, which is essential to understand the phenological processes of exploited species and their potential shifts due to environmental changes.

Twelve Recommendations for Advancing Marine Conservation in European and Contiguous Seas - Stelios Katsanevakis; Marta Coll; Simonetta Fraschetti; Sylvaine Giakoumi; David Goldsborough; Vesna Mačić; Peter Mackelworth; Gil Rilov; Vanessa Stelzenmüller; Paolo G. Albano; Amanda E. Bates; Stanislao Bevilacqua; et al. (Frontiers in Marine Science, 2020)

Advancing Global Ecological Modeling Capabilities to Simulate Future Trajectories of Change in Marine Ecosystems - Marta Coll; Jeroen Steenbeek; Maria Grazia Pennino; Joe Buszowski; Kristin Kaschner; Heike K. Lotze; Yannick Rousseau; Derek P. Tittensor; Carl Walters; Reg A. Watson; Villy Christensen (Frontiers in Marine Science, 2020)

The Ocean Decade: A True Ecosystem Modeling Challenge - Johanna J. Heymans; Alida Bundy; Villy Christensen; Marta Coll; Kim de Mutsert; Elizabeth A. Fulton; Chiara Piroddi; Yunne-Jai Shin; Jeroen Steenbeek; Morgane Travers-Trolet (Frontiers in Marine Science, 2020)

Exploring Temporal Variability in the Southern Benguela Ecosystem Over the Past Four Decades Using a Time-Dynamic Ecosystem Model - Lynne J. Shannon; Kelly Ortega-Cisneros; Tarron Lamont; Henning Winker; Robert Crawford; Astrid Jarre; Marta Coll (Frontiers in Marine Science, 2020)

Current and Future Influence of Environmental Factors on Small Pelagic Fish Distributions in the Northwestern Mediterranean Sea - Maria Grazia Pennino; Marta Coll; Marta Albo-Puigserver; Elena Fernández-Corredor; Jeroen Steenbeek; Ana Giráldez; María González; Antonio Esteban; José M. Bellido (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Recovery Debts Can Be Revealed by Ecosystem Network-Based Approaches - Mélodie Dubois; Didier Gascuel; Marta Coll; Joachim Claudet (Ecosystems, 2019)

Assessing fishing impacts in a tropical reservoir through an ecosystem modeling approach - Juliana Strieder Philippsen; Carolina V. Minte-Vera; Marta Coll; Ronaldo Angelini (Reviews in Fish Biology and Fisheries, 2019)

Twenty‐first‐century climate change impacts on marine animal biomass and ecosystem structure across ocean basins - Andrea Bryndum‐Buchholz; Derek P. Tittensor; Julia L. Blanchard; William W. L. Cheung; Marta Coll; Eric D. Galbraith; Simon Jennings; Olivier Maury; Heike K. Lotze (Global Change Biology, 2019)
Climate change effects on marine ecosystems include impacts on primary production, ocean temperature, species distributions, and abundance at local to global scales. These changes will significantly alter marine ecosystem structure and function with associated socio‐economic impacts on ecosystem services, marine fisheries, and fishery‐dependent societies. Yet how these changes may play out among ocean basins over the 21st century remains unclear, with most projections coming from single ecosystem models that do not adequately capture the range of model uncertainty. We address this by using six marine ecosystem models within the Fisheries and Marine Ecosystem Model Intercomparison Project (Fish‐MIP) to analyze responses of marine animal biomass in all major ocean basins to contrasting climate change scenarios. Under a high emissions scenario (RCP8.5), total marine animal biomass declined by an ensemble mean of 15%–30% (±12%–17%) in the North and South Atlantic and Pacific, and the Indian Ocean by 2100, whereas polar ocean basins experienced a 20%–80% (±35%–200%) increase. Uncertainty and model disagreement were greatest in the Arctic and smallest in the South Pacific Ocean. Projected changes were reduced under a low (RCP2.6) emissions scenario. Under RCP2.6 and RCP8.5, biomass projections were highly correlated with changes in net primary production and negatively correlated with projected sea surface temperature increases across all ocean basins except the polar oceans. Ecosystem structure was projected to shift as animal biomass concentrated in different size‐classes across ocean basins and emissions scenarios. We highlight that climate change mitigation measures could moderate the impacts on marine animal biomass by reducing biomass declines in the Pacific, Atlantic, and Indian Ocean basins. The range of individual model projections emphasizes the importance of using an ensemble approach in assessing uncertainty of future change.

Food web changes associated with drought and invasive species in a tropical semiarid reservoir - Luis Artur Valões Bezerra; Ronaldo Angelini; Jean Ricardo Simões Vitule; Marta Coll; Jorge Iván Sánchez-Botero (Hydrobiologia, 2018)

Ecological role and historical trends of large pelagic predators in a subtropical marine ecosystem of the South Atlantic - Hugo Bornatowski; Ronaldo Angelini; Marta Coll; Rodrigo R. P. Barreto; Alberto F. Amorim (Reviews in Fish Biology and Fisheries, 2018)

Regional-Scale Differences in Eutrophication Effects on Eelgrass-Associated (Zostera marina) Macrofauna - Allison L. Schmidt; Marta Coll; Heike K. Lotze (Estuaries and Coasts, 2017)

Strong fisheries management and governance positively impact ecosystem status - Alida Bundy; Ratana Chuenpagdee; Jennifer L Boldt; Maria de Fatima Borges; Mohamed Lamine Camara; Marta Coll; Ibrahima Diallo; Clive Fox; Elizabeth A Fulton; Ayse Gazihan; Astrid Jarre; Didier Jouffre; et al. (Fish and Fisheries, 2017)
Fisheries have had major negative impacts on marine ecosystems, and effective fisheries management and governance are needed to achieve sustainable fisheries, biodiversity conservation goals and thus good ecosystem status. To date, the IndiSeas programme (Indicators for the Seas) has focussed on assessing the ecological impacts of fishing at the ecosystem scale using ecological indicators. Here, we explore fisheries ‘Management Effectiveness’ and ‘Governance Quality’ and relate this to ecosystem health and status. We developed a dedicated expert survey, focused at the ecosystem level, with a series of questions addressing aspects of management and governance, from an ecosystem‐based perspective, using objective and evidence‐based criteria. The survey was completed by ecosystem experts (managers and scientists) and results analysed using ranking and multivariate methods. Results were further examined for selected ecosystems, using expert knowledge, to explore the overall findings in greater depth. Higher scores for ‘Management Effectiveness’ and ‘Governance Quality’ were significantly and positively related to ecosystems with better ecological status. Key factors that point to success in delivering fisheries and conservation objectives were as follows: the use of reference points for management, frequent review of stock assessments, whether Illegal, Unreported and Unregulated ( IUU ) catches were being accounted for and addressed, and the inclusion of stakeholders. Additionally, we found that the implementation of a long‐term management plan, including economic and social dimensions of fisheries in exploited ecosystems, was a key factor in successful, sustainable fisheries management. Our results support the thesis that good ecosystem‐based management and governance, sustainable fisheries and healthy ecosystems go together.

Ecosystem effects of invertebrate fisheries - Tyler D Eddy; Heike K Lotze; Elizabeth A Fulton; Marta Coll; Cameron H Ainsworth; Júlio Neves de Araújo; Catherine M Bulman; Alida Bundy; Villy Christensen; John C Field; Neil A Gribble; Mejs Hasan; et al. (Fish and Fisheries, 2017)
Since the 1950s, invertebrate fisheries catches have rapidly expanded globally to more than 10 million tonnes annually, with twice as many target species, and are now significant contributors to global seafood provision, export, trade and local livelihoods. Invertebrates play important and diverse functional roles in marine ecosystems, yet the ecosystem effects of their exploitation are poorly understood. Using 12 ecosystem models distributed worldwide, we analysed the trade‐offs of various invertebrate fisheries and their ecosystem effects as well as ecological indicators. Although less recognized for their contributions to marine food webs, our results show that the magnitude of trophic impacts of invertebrates on other species of commercial and conservation interest is comparable with those of forage fish. Generally, cephalopods showed the strongest ecosystem effects and were characterized by a strong top‐down predatory role. Lobster, and to a lesser extent, crabs, shrimp and prawns, also showed strong ecosystem effects, but at lower trophic levels. Benthic invertebrates, including epifauna and infauna, also showed considerable ecosystem effects, but with strong bottom‐up characteristics. In contrast, urchins, bivalves, and gastropods showed generally lower ecosystem effects in our simulations. Invertebrates also strongly contributed to benthic–pelagic coupling, with exploitation of benthic invertebrates impacting pelagic fishes and vice versa. Finally, on average, invertebrates produced maximum sustainable yield at lower levels of depletion (~45%) than forage fish (~65%), highlighting the need for management targets that avoid negative consequences for target species and marine ecosystems as a whole.

Differences in the relative roles of environment, prey availability and human activity in the spatial distribution of two marine mesopredators living in highly exploited ecosystems - Joan Navarro; Laura Cardador; Ángel M. Fernández; José M. Bellido; Marta Coll (Journal of Biogeography, 2016)
Aim Identifying the main factors affecting the spatial distribution of marine predators is essential in order to evaluate their distribution patterns, predict the potential impact of human activities on their populations and design accurate management actions. This information is also valuable from a more general management perspective, as marine predators are often considered indicators of habitat quality. In this context, we aimed to determine the degree to which environmental features, prey availability and human activities interact and influence spatial distribution of two marine mesopredator elasmobranchs, the small‐spotted catshark ( Scyliorhinus canicula ) and the Mediterranean starry ray ( Raja asterias ), living in a highly human‐exploited environment. Location Mediterranean Sea. Methods With information obtained from an extended experimental survey, we investigated the relative importance of environmental variables, prey availability and human activities on the spatial distribution of the abundance, biomass and occurrence rate of these marine mesopredators using deviance partitioning analyses. Results Our results revealed that environmental variables were the most important factors explaining the spatial distribution of Mediterranean starry ray, whereas small‐spotted catshark distribution was also influenced by prey availability and human factors. From a management point of view, these findings suggest that Mediterranean starry ray could be a good candidate as an indicator species of demersal environmental quality. On the other hand, the distribution of the small‐spotted catshark, which responds in an interactive and complex way to environment, prey availability and particular human activities, may be misleading as an environmental indicator. Main conclusions The spatial distribution of elasmobranchs in highly human‐impacted marine areas can reflect the interactive and combined effects of multiple factors. To avoid misunderstandings, attention should be paid to statistical procedures allowing the separation of pure and joint contribution of the factors driving the observed spatial patterns.

Fishing impact and environmental status in E uropean seas: a diagnosis from stock assessments and ecosystem indicators - Didier Gascuel; Marta Coll; Clive Fox; Sylvie Guénette; Jérome Guitton; Andrew Kenny; Leyla Knittweis; J Rasmus Nielsen; Gerjan Piet; Tiit Raid; Morgane Travers‐Trolet; Samuel Shephard (Fish and Fisheries, 2016)
Stock‐based and ecosystem‐based indicators are used to provide a new diagnosis of the fishing impact and environmental status of E uropean seas. In the seven European marine ecosystems covering the B altic and the N orth‐east A tlantic, (i) trends in landings since 1950 were examined; (ii) syntheses of the status and trends in fish stocks were consolidated at the ecosystem level; and (iii) trends in ecosystem indicators based on landings and surveys were analysed. We show that yields began to decrease everywhere (except in the B altic) from the mid‐1970s, as a result of the over‐exploitation of some major stocks. Fishermen adapted by increasing fishing effort and exploiting a wider part of the ecosystems. This was insufficient to compensate for the decrease in abundance of many stocks, and total landings have halved over the last 30 years. The highest fishing impact took place in the late 1990s, with a clear decrease in stock‐based and ecosystem indicators. In particular, trophic‐based indicators exhibited a continuous decreasing trend in almost all ecosystems. Over the past decade, a decrease in fishing pressure has been observed, the mean fishing mortality rate of assessed stocks being almost halved in all the considered ecosystems, but no clear recovery in the biomass and ecosystem indicators is yet apparent. In addition, the mean recruitment index was shown to decrease by around 50% in all ecosystems (except the B altic). We conclude that building this kind of diagnosis is a key step on the path to implementing an ecosystem approach to fisheries management.

Exploring the links between forest transition and landscape changes in the Mediterranean. Does forest recovery really lead to better landscape quality? - Joan Marull; Iago Otero; Constantí Stefanescu; Enric Tello; Marta Miralles; Francesc Coll; Manel Pons; Giovanna L. Diana (Agroforestry Systems, 2015)

Towards a framework for assessment and management of cumulative human impacts on marine food webs - Sylvaine Giakoumi; Benjamin S. Halpern; Loïc N. Michel; Sylvie Gobert; Maria Sini; Charles‐François Boudouresque; Maria‐Cristina Gambi; Stelios Katsanevakis; Pierre Lejeune; Monica Montefalcone; Gerard Pergent; Christine Pergent‐Martini; et al. (Conservation Biology, 2015)
Effective ecosystem‐based management requires understanding ecosystem responses to multiple human threats, rather than focusing on single threats. To understand ecosystem responses to anthropogenic threats holistically, it is necessary to know how threats affect different components within ecosystems and ultimately alter ecosystem functioning. We used a case study of a Mediterranean seagrass (Posidonia oceanica) food web and expert knowledge elicitation in an application of the initial steps of a framework for assessment of cumulative human impacts on food webs. We produced a conceptual seagrass food web model, determined the main trophic relationships, identified the main threats to the food web components, and assessed the components’ vulnerability to those threats. Some threats had high (e.g., coastal infrastructure) or low impacts (e.g., agricultural runoff) on all food web components, whereas others (e.g., introduced carnivores) had very different impacts on each component. Partitioning the ecosystem into its components enabled us to identify threats previously overlooked and to reevaluate the importance of threats commonly perceived as major. By incorporating this understanding of system vulnerability with data on changes in the state of each threat (e.g., decreasing domestic pollution and increasing fishing) into a food web model, managers may be better able to estimate and predict cumulative human impacts on ecosystems and to prioritize conservation actions.

The global ocean is an ecosystem: simulating marine life and fisheries - Villy Christensen; Marta Coll; Joe Buszowski; William W. L. Cheung; Thomas Frölicher; Jeroen Steenbeek; Charles A. Stock; Reg A. Watson; Carl J. Walters (Global Ecology and Biogeography, 2015)
Aim There has been considerable effort allocated to understanding the impact of climate change on our physical environment, but comparatively little to how life on Earth and ecosystem services will be affected. Therefore, we have developed a spatial–temporal food web model of the global ocean, spanning from primary producers through to top predators and fisheries. Through this, we aim to evaluate how alternative management actions may impact the supply of seafood for future generations. Location Global ocean. Methods We developed a modelling complex to initially predict the combined impact of environmental parameters and fisheries on global seafood production, and initially evaluated the model's performance through hindcasting. The modelling complex has a food web model as core, obtains environmental productivity from a biogeochemical model and assigns global fishing effort spatially. We tuned model parameters based on M arkov chain random walk stock reduction analysis, fitting the model to historic catches. We evaluated the goodness‐of‐fit of the model to data for major functional groups, by spatial management units and globally. Results This model is the most detailed ever constructed of global fisheries, and it was able to replicate broad patterns of historic fisheries catches with best agreement for the total catches and good agreement for species groups, with more variation at the regional level. Main conclusions We have developed a modelling complex that can be used for evaluating the combined impact of fisheries and climate change on upper‐trophic level organisms in the global ocean, including invertebrates, fish and other large vertebrates. The model provides an important step that will allow global‐scale evaluation of how alternative fisheries management measures can be used for mitigation of climate change.

Overlooked impacts and challenges of the new E uropean discard ban - Francesc Sardà; Marta Coll; Johanna J Heymans; Konstantinos I Stergiou (Fish and Fisheries, 2015)
Discards are the portion of animal and plant material in the catch that is dumped back at sea. The C ommon F isheries P olicy plan proposed by the E uropean C ommission for 2014–2020 presents a controversial goal: to enforce the landing of fishing discards as a measure to encourage their reduction. This historical and political decision will shape the future of the fishing exploitation in E uropean S eas. Discards generated by E uropean fleets are not negligible, and its reduction is an ecological, socioeconomical and moral imperative. However, it must be achieved through the reduction in discards at source and the promotion of selective and non‐destructive gears. We argue it is doubtful that this discard ban will result in an effective reduction of discards. The proposed measure may, in fact, negatively affect ecosystems at all levels of biological hierarchy by disregarding the E cosystem‐ B ased A pproach to F isheries and the P recautionary P rinciple. It could negatively impact several species by increasing fishing mortality, also commercial species if discards are not accounted in the total allowable catch. Communities preying on discards will likely be affected. The role discards currently play in the energy turnover of current ecosystems will be modified and should be fully evaluated. The landing of discards will likely generate new markets of fishmeal due to the growing demands for marine living resources. The ban will require substantial public investment to deal with technical problems on board and to control and enforce. Therefore, this measure should be only implemented after rigorous scientific and technical studies have been developed.

‘Low‐hanging fruit’ for conservation of marine vertebrate species at risk in the M editerranean S ea - Marta Coll; Jeroen Steenbeek; Frida Ben Rais Lasram; David Mouillot; Philippe Cury (Global Ecology and Biogeography, 2015)
Aim Conservation priorities need to take the feasibility of protection measures into account. In times of economic pressure it is essential to identify the ‘low‐hanging fruit’ for conservation: areas where human impacts are lower and biological diversity is still high, and thus conservation is more feasible. Location We used the M editerranean large marine ecosystem ( LME ) as a case study to identify the overlapping areas of low threats and high diversity of vertebrate species at risk. Methods This LME is the first in the world to have a complete regional IUCN Red List assessment of the native marine fish. We augmented these data with distributions of marine mammals, marine turtles and seabirds at risk, and we calculated the spatial distributions of species at risk ( IUCN densities). Using cumulative threats we identified ‘priority areas for conservation of species at risk’ ( PACS ), where IUCN diversities are high and threats are low. We assessed whether IUCN diversities and PACS were spatially congruent among taxa and we quantified whether PACS corresponded to current and proposed protected areas. Results IUCN densities and PACS were not highly correlated spatially among taxa. Continental shelves and deep‐sea slopes of the A lboran S ea, western M editerranean and T unisian P lateau/ G ulf of Sidra are identified as relevant for fish species at risk. The eastern side of the western M editerranean and the Adriatic Sea are identified as most relevant for endemic fish, and shelf and open sea areas distributed through the LME are most important for marine mammals and turtles at risk, while specific locations of the western M editerranean S ea and the A egean and L evantine seas are highlighted for seabirds. Main conclusions Large parts of the areas of PACS fell outside current or proposed frameworks to be prioritized for conservation. PACS may be suitable candidates for contributing to the 10% protection target for the M editerranean S ea by 2020.

Representing Variable Habitat Quality in a Spatial Food Web Model - Villy Christensen; Marta Coll; Jeroen Steenbeek; Joe Buszowski; Dave Chagaris; Carl J. Walters (Ecosystems, 2014)

Invading the Mediterranean Sea: biodiversity patterns shaped by human activities - Stelios Katsanevakis; Marta Coll; Chiara Piroddi; Jeroen Steenbeek; Frida Ben Rais Lasram; Argyro Zenetos; Ana Cristina Cardoso (Frontiers in Marine Science, 2014)

Short- and long-term importance of small sharks in the diet of the rare deep-sea shark Dalatias licha - Joan Navarro; Lourdes López; Marta Coll; Claudio Barría; Raquel Sáez-Liante (Marine Biology, 2014)

Large‐scale recruitment limitation in M editerranean pines: the role of Q uercus ilex and forest successional advance as key regional drivers - Jofre Carnicer; Marta Coll; Xavier Pons; Miquel Ninyerola; Jordi Vayreda; Josep Peñuelas (Global Ecology and Biogeography, 2014)
Aim Large‐scale patterns of limitations in tree recruitment remain poorly described in the M editerranean B asin, and this information is required to assess the impacts of global warming on forests. Here, we unveil the existence of opposite trends of recruitment limitation between the dominant genera Q uercus and P inus on a large scale and identify the key ecological drivers of these diverging trends. Location S pain Methods We gathered data from the S panish N ational F orest inventory to assess recruitment trends for the dominant species ( P inus halepensis , P inus pinea , P inus pinaster , P inus nigra , P inus sylvestris , P inus uncinata , Q uercus suber , Q uercus ilex , Q uercus petraea , Q uercus robur , Q uercus faginea and Q uercus pyrenaica ). We assessed the direct and indirect drivers of recruitment by applying B ayesian structural equation modelling techniques. Results Severe limitations in recruitment were observed across extensive areas for all P inus species studied, with recruitment failure affecting 54–71% of the surveyed plots. In striking contrast, Q uercus species expanded into 41% of the plots surveyed compared to only 10% for P inus and had a lower local recruitment failure (29% of Q uercus localities compared to 63% for P inus species). Bayesian structural equation models highlighted the key role of the presence of Q . ilex saplings and the increase in the basal area of Q . ilex in limiting recruitment in five P inus species. The recruitment of P . sylvestris and P . nigra showed the most negative trends and was negatively associated with the impacts of fire. Main conclusions This study identified Q . ilex , the most widespread species in this area, as a key driver of recruitment shifts on a large scale, negatively affecting most pine species with the advance of forest succession. These results highlight that the future expansion/contraction of Q . ilex stands with ongoing climate change will be a key process indirectly controlling the demographic responses of P inus species in the M editerranean B asin.

From projected species distribution to food‐web structure under climate change - Camille Albouy; Laure Velez; Marta Coll; Francesco Colloca; François Le Loc'h; David Mouillot; Dominique Gravel (Global Change Biology, 2014)
Climate change is inducing deep modifications in species geographic ranges worldwide. However, the consequences of such changes on community structure are still poorly understood, particularly the impacts on food‐web properties. Here, we propose a new framework, coupling species distribution and trophic models, to predict climate change impacts on food‐web structure across the Mediterranean Sea. Sea surface temperature was used to determine the fish climate niches and their future distributions. Body size was used to infer trophic interactions between fish species. Our projections reveal that 54 fish species of 256 endemic and native species included in our analysis would disappear by 2080–2099 from the Mediterranean continental shelf. The number of feeding links between fish species would decrease on 73.4% of the continental shelf. However, the connectance of the overall fish web would increase on average, from 0.26 to 0.29, mainly due to a differential loss rate of feeding links and species richness. This result masks a systematic decrease in predator generality, estimated here as the number of prey species, from 30.0 to 25.4. Therefore, our study highlights large‐scale impacts of climate change on marine food‐web structure with potential deep consequences on ecosystem functioning. However, these impacts will likely be highly heterogeneous in space, challenging our current understanding of climate change impact on local marine ecosystems.

The scientific strategy needed to promote a regional ecosystem-based approach to fisheries in the Mediterranean and Black Seas - Marta Coll; Philippe Cury; Ernesto Azzurro; Michel Bariche; Giorgos Bayadas; Jose Maria Bellido; Christian Chaboud; Joachim Claudet; Abdel-Fattah El-Sayed; Didier Gascuel; Leyla Knittweis; Carlo Pipitone; et al. (Reviews in Fish Biology and Fisheries, 2013)

Feeding ecology and trophic position of a Mediterranean endemic ray: consistency between sexes, maturity stages and seasons - Joan Navarro; Marta Coll; Marc Preminger; Isabel Palomera (Environmental Biology of Fishes, 2013)

Exploring Patterns of Seafood Provision Revealed in the Global Ocean Health Index - Kristin M. Kleisner; Catherine Longo; Marta Coll; Ben S. Halpern; Darren Hardy; Steven K. Katona; Frédéric Le Manach; Daniel Pauly; Andrew A. Rosenberg; Jameal F. Samhouri; Courtney Scarborough; U. Rashid Sumaila; et al. (Ambio, 2013)

Evidence of current impact of climate change on life: a walk from genes to the biosphere - Josep Peñuelas; Jordi Sardans; Marc Estiarte; Romà Ogaya; Jofre Carnicer; Marta Coll; Adria Barbeta; Albert Rivas‐Ubach; Joan Llusià; Martin Garbulsky; Iolanda Filella; Alistair S. Jump (Global Change Biology, 2013)
We review the evidence of how organisms and populations are currently responding to climate change through phenotypic plasticity, genotypic evolution, changes in distribution and, in some cases, local extinction. Organisms alter their gene expression and metabolism to increase the concentrations of several antistress compounds and to change their physiology, phenology, growth and reproduction in response to climate change. Rapid adaptation and microevolution occur at the population level. Together with these phenotypic and genotypic adaptations, the movement of organisms and the turnover of populations can lead to migration toward habitats with better conditions unless hindered by barriers. Both migration and local extinction of populations have occurred. However, many unknowns for all these processes remain. The roles of phenotypic plasticity and genotypic evolution and their possible trade‐offs and links with population structure warrant further research. The application of omic techniques to ecological studies will greatly favor this research. It remains poorly understood how climate change will result in asymmetrical responses of species and how it will interact with other increasing global impacts, such as N eutrophication, changes in environmental N : P ratios and species invasion, among many others. The biogeochemical and biophysical feedbacks on climate of all these changes in vegetation are also poorly understood. We here review the evidence of responses to climate change and discuss the perspectives for increasing our knowledge of the interactions between climate change and life.

An ocean observation system for monitoring the affects of climate change on the ecology and sustainability of pelagic fisheries in the Pacific Ocean - Simon J. Nicol; Valerie Allain; Graham M. Pilling; Jeff Polovina; Marta Coll; Johann Bell; Paul Dalzell; Peter Sharples; Robert Olson; Shane Griffiths; Jeffrey M. Dambacher; Jock Young; et al. (Climatic Change, 2013)

Advancing marine conservation planning in the Mediterranean Sea - Sylvaine Giakoumi; Tessa Mazor; Simonetta Fraschetti; Salit Kark; Michelle Portman; Marta Coll; Jeroen Steenbeek; Hugh Possingham (Reviews in Fish Biology and Fisheries, 2012)

Global in scope and regionally rich: an IndiSeas workshop helps shape the future of marine ecosystem indicators - Yunne-Jai Shin; Alida Bundy; Lynne J. Shannon; Julia L. Blanchard; Ratana Chuenpagdee; Marta Coll; Ben Knight; Christopher Lynam; Gerjan Piet; Anthony J. Richardson (Reviews in Fish Biology and Fisheries, 2012)

The Mediterranean Sea under siege: spatial overlap between marine biodiversity, cumulative threats and marine reserves - Marta Coll; Chiara Piroddi; Camille Albouy; Frida Ben Rais Lasram; William W. L. Cheung; Villy Christensen; Vasiliki S. Karpouzi; François Guilhaumon; David Mouillot; Michelle Paleczny; Maria Lourdes Palomares; Jeroen Steenbeek; et al. (Global Ecology and Biogeography, 2012)
Aim A large body of knowledge exists on individual anthropogenic threats that have an impact on marine biodiversity in the Mediterranean Sea, although we know little about how these threats accumulate and interact to affect marine species and ecosystems. In this context, we aimed to identify the main areas where the interaction between marine biodiversity and threats is more pronounced and to assess their spatial overlap with current marine protected areas in the Mediterranean. Location Mediterranean Sea. Methods We first identified areas of high biodiversity of marine mammals, marine turtles, seabirds, fishes and commercial or well‐documented invertebrates. We mapped potential areas of high threat where multiple threats are occurring simultaneously. Finally we quantified the areas of conservation concern for biodiversity by looking at the spatial overlap between high biodiversity and high cumulative threats, and we assessed the overlap with protected areas. Results Our results show that areas with high marine biodiversity in the Mediterranean Sea are mainly located along the central and north shores, with lower values in the south‐eastern regions. Areas of potential high cumulative threats are widespread in both the western and eastern basins, with fewer areas located in the south‐eastern region. The interaction between areas of high biodiversity and threats for invertebrates, fishes and large animals in general (including large fishes, marine mammals, marine turtles and seabirds) is concentrated in the coastal areas of Spain, Gulf of Lions, north‐eastern Ligurian Sea, Adriatic Sea, Aegean Sea, south‐eastern Turkey and regions surrounding the Nile Delta and north‐west African coasts. Areas of concern are larger for marine mammal and seabird species. Main conclusions These areas may represent good candidates for further research, management and protection activities, since there is only a maximum 2% overlap between existing marine protected areas (which cover 5% of the Mediterranean Sea) and our predicted areas of conservation concern for biodiversity.

International workshop on opportunities for ecosystem approaches to fisheries management in the Pacific Ocean tuna fisheries - Valerie Allain; Simon Nicol; Jeffrey Polovina; Marta Coll; Robert Olson; Shane Griffiths; Jeffrey Dambacher; Jock Young; Jesus Jurado Molina; Simon Hoyle; Tim Lawson (Reviews in Fish Biology and Fisheries, 2012)

Trophic and functional cascades in tropical versus temperate aquatic microcosms - Marta Coll; Kevin Hargadon (Aquatic Ecology, 2012)

Contributions of food web modelling to the ecosystem approach to marine resource management in the Mediterranean Sea - Marta Coll; Simone Libralato (Fish and Fisheries, 2012)
Ecological modelling tools are applied worldwide to support the ecosystem‐based approach of marine resources (EAM). In the last decades, numerous applications were attempted in the Mediterranean Sea, mainly using the Ecopath with Ecosim ( EwE ) tool. These models were used to analyse a variety of complex environmental problems. Many applications analysed the ecosystem impacts of fishing and assessed management options. Other studies dealt with the accumulation of pollution through the food web, the impact of aquaculture or the ecosystem effects of climate change. They contributed to the scientific aspects of an ecosystem‐based approach in the region because they integrated human activities within an ecosystem context and evaluated their impact on the marine food web, including environmental factors. These studies also gathered a significant amount of information at an ecosystem level. Thus, in the second part of this review, we used this information to quantify structural and functional traits of Mediterranean marine ecosystems at regional scales as the illustration of further potentialities of EwE for an EAM. Results highlighted differential traits between ecosystem types and a few between basins, which illustrate the environmental heterogeneity of the Mediterranean Sea. Moreover, our analysis evidenced the importance of top predators and small pelagic fish in Mediterranean ecosystems, in addition to the structural role of benthos and plankton organisms. The impact of fishing was high and of a similar intensity in the western, central and eastern regions and showed differences between ecosystem types. The keystone role of species was more prominent in protected environments.

Historical Changes in Marine Resources, Food-web Structure and Ecosystem Functioning in the Adriatic Sea, Mediterranean - Heike K. Lotze; Marta Coll; Jennifer A. Dunne (Ecosystems, 2011)

Structural Degradation in Mediterranean Sea Food Webs: Testing Ecological Hypotheses Using Stochastic and Mass-Balance Modelling - Marta Coll; Heike K. Lotze; Tamara N. Romanuk (Ecosystems, 2008)